Alternative-renewable energy in shipping - economic aspect - Huang, Junjie. (2013)
The deterioration of the environment has pressed industries globally to take actions. Shipping activities has been viewed as one of those with significant environmental impacts. As a result, international organizations like the International Maritime Organization (IMO) have been enforcing stricter environmental protection regulations. The uncertainty of supply of fossil fuel is another one of the concerns towards the use of bunker fuel. Alternative energy seem to be the optimum solution amidst these challenges.